TIDAK TERSAJI :The Implementation of character building as guidance and counseling programs in SDIT Ulul Albab Pekalongan - RAFIKA BUDIATI (Jurusan Tarbiyah - Pendidikan Agama Islam - STAIN Pekalongan, 2008)
Human is Allahs creature with potentials. Allah gives human them to be improved as by education. Education has same purpose with guidance. Guidance purpose is to guide students to reach optimun achievements. SDIT Ulul Albab chooses guidance and counseling model, it is character building. Character building is an integrated learning package that is designed to help students in learning more about humanity values, particularly the connected values with humans good behaviour and attitude. Problem examined in this research are how character building becomes program in guidance and counseling in SDIT Ulul Albab Pekalongan, how the background of its implementation and planning, aim, phases, and activities to implement it, the significance, programs and inhibiting and supporting factors in character building. The research used approach is qualitative approach with field research. The result is character building can be a model of guidance and counseling in SDIT Ulul Albab. Character building becomes a process of personality improvement by creating effective situation of learning and instruction, also becomes a way to make positive activities as students habits wherever they are. Character building also becomes a lesson at school, so students do not only know and understand about this lesson, but they also have to implement its substance. Some determined factors of character building are models or examples of teacher, parents and society.